PEMANFAATAN MEDIA INTERAKTIF DIGITAL BERBASIS CANVA DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Tati Alifah Ratnamaya; Siti Mayang Sari; T. M Haekal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the utilization of Canva-based interactive digital media in Social Studies (IPS) learning in the fifth grade of elementary school. The research subjects consisted of 32 fifth-grade students. The method used in this study was a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. The results of the study indicate that the use of Canva as a learning medium is able to increase student engagement, facilitate the understanding of learning materials, and create a more interesting and interactive learning environment. Therefore, Canva-based media can be used as an innovative alternative in Social Studies learning at the elementary school level.